2019
DOI: 10.1002/app.48138
|View full text |Cite
|
Sign up to set email alerts
|

Determination of modified polyamide 6's foaming windows by bubble growth simulations based on rheological measurements

Abstract: Reactive extrusion was used to modify virgin polyamides 6 (v-PA6) and to prepare chain extended PA6 (CE-PA6) and longchain branched PA6 (LCB-PA6) for the melt foaming process. This was done using a twin-screw extruder and the following modifiers: a chain extender ADR-4368 and a branching agent maleic anhydride grafted polypropylene. A reaction mechanism was proposed to explain the chain extension and long-chain branching reactions and was verified by the Fourier transform infrared spectroscopy data. The analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 48 publications
1
30
0
Order By: Relevance
“…In contrast, the strain hardening behavior is caused by the LCB structure. Xu et al 42 obtained the long‐chain structure and LCB structure through grafted modification of PA6 and then confirmed through uniaxial tensile rheology that the long‐chain structure did not produce strain hardening behavior, which is caused by the LCB structure. Therefore, tensile rheology can effectively distinguish the existence of LCB structures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the strain hardening behavior is caused by the LCB structure. Xu et al 42 obtained the long‐chain structure and LCB structure through grafted modification of PA6 and then confirmed through uniaxial tensile rheology that the long‐chain structure did not produce strain hardening behavior, which is caused by the LCB structure. Therefore, tensile rheology can effectively distinguish the existence of LCB structures.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it is not clear whether the | η *| and G′ of modified composites are increased compared with PPC, and whether these changes are caused by the long chain or branched molecular structure. Shear rheology analysis provides sufficient information of molecular weight and molecular weight distribution, but uniaxial tensile rheology is more sensitive to the branched molecular structure than dynamic shear rheology 42 . The best way to prove the existence of branched structure is to observe the occurrence of strain hardening through tensile rheological measurements.…”
Section: Resultsmentioning
confidence: 99%
“…The loss tangent shown in Figure 8 b also decreased with the formation of long chain branches in the presence of chain extender. The loss tangent has an inverse relationship with the melt strength, which affects the melt processing properties [ 32 ]. That is, the melt processability of PA6 was enhanced by the addition of ADR due to the formation of long chain branches.…”
Section: Resultsmentioning
confidence: 99%
“…They found that the PTFE nanofibrils network was effective cell nucleating agent. However, according to our knowledge, only a few reports on polyamide 6 foam using batch foaming method assist by scCO 2 were reported 14,15,35,36 . The influence of PTFE in PA6 foams was unclear.…”
Section: Introductionmentioning
confidence: 96%